An empirical study to evaluate students' conceptual modeling skills using UML. Issue 4 (2nd October 2019) - Aljumaily, Harith; Cuadra, Dolores; Laefer, Debra F.
ABSTRACT: Background : Conceptual models are an essential phase in software design, but they can create confusion and reduced performance for students in Database Design courses. Objective : A novel Relational Data Model Validation Tool (MVTool) was developed and tested to determine (1) if students who use MVTool perform better than those who do not, and (2) if design skills improve after using MVTool. Method : After a pre-test of database design skills, 68 students were divided into matched-pair control and experimental groups. All completed a database design task, with the experimental group having access to MVTool and the control group having no access to the tool. Findings : Notable improvements in specific design skills could be consistently detected in students after the introduction of the tool. Implications : Validation tools such as MVTool may help students to understand modeling languages and conventions used in database design, thereby improving their skill development and course outcomes.